Changes in T lymphocyte subsets in patients with acute neuromyelitis optica spectrum disorder - Shao, Ying-Zhe; Tan, Tao-Feng; Zhang, Lin-Jie; Zhao, Ning; Yang, Li; Zhang, Qiu-Xia (Frontiers in Immunology, 2025)
BackgroundNeuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune disease of the central nervous system, primarily characterized by anti-AQP4 antibodies. While, treatment for preventing recurrence of NMOSD predominantly focuses on the production of anti-AQP4 antibodies and the subsequent inflammatory response, one effective strategy is targeting B cells, investigating the status of T lymphocytes during NMOSD onset holds significant importance for elucidating disease mechanisms and identifying potential novel therapeutic approaches.MethodsPeripheral blood samples were collected from NMOSD patients with acute exacerbation. The NMOSD patients were divided into the pre- glucocorticoid treatment NMOSD patient group (PRE) and the glucocorticoid treatment NMOSD patient group (GC) based on whether they received glucocorticoid therapy. Healthy controls were included at the same time. Flow cytometry was employed to analyze differences in T cell compartment.ResultsMultivariate linear regression analysis adjusted for age revealed that the GC group had fewer CD8+ TEM cells than controls (β=-14.96, P=0.002). In addition, the PRE group had higher frequencies of HLA-DR+CD38+ CD4+ cells and HLA-DR+ CD4+ T cells compared to the control group (P= 0.005, P= 0.004, respectively), the frequency of HLA-DR+ CD4+ T cells in PRE group was higher than the GC group (P= 0.007). The multivariate analysis results showed that in CD4+ T cells, the frequency of Th1Th17 cells in the PRE patient group was higher than that in the control group (β= 6.37, 98.33% CI:1.96-10.78, P = 0.001), and the frequency of Th2 cells in the PRE group was lower than that in the control group (β=-11.41, 98.33% CI: -22.26– -0.55, P = 0.012).ConclusionThese findings underscore the pivotal role of Th1Th17 and Th17 cells in NMOSD pathogenesis. Exploring intervention strategies targeting Th17 cells or T cell activation (e.g., HLA-DR-targeted therapies) may hold clinical relevance.